Analyzing the effectiveness of IDS/IPS in real-time with a custom in-vehicle design - Adu-Kyere, Akwasi; Nigussie, Ethiopia; Isoaho, Jouni (Netherlands, 2025)
The era of ubiquitously interconnected, intelligent, and self-driving automobiles approaches as contemporary vehicles undergo gradual enhancements in terms of security catalyzed by security analysis in various modules, algorithms, operating systems, and soft and hardware nodes. This work examines the application of a dynamic Intrusion Detection System (IDS) and Intrusion Prevention System (IPS) in real-time using a Renault T520 Heavy-duty truck. It assesses the effectiveness of the security analysis procedure and its execution, focusing on the quality of the analysis concerning data derived from experiment sources. The validation of the security implementation adheres to a unified inbound and outbound.
The 15th International Conference on Ambient Systems, Networks and Technologies Networks (ANT) / The 7th International Conference on Emerging Data and Industry 4.0 (EDI40), April 23-25, 2024, Hasselt University, Belgium